2014
DOI: 10.4137/ijtr.s13958
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic Acid Levels in Cerebrospinal Fluid from Patients with Alzheimer's Disease or Dementia with Lewy Bodies

Abstract: Kynurenic acid (KYNA) is implicated in cognitive functions. Altered concentrations of the compound are found in serum and cerebrospinal fluid (CSF) of patients with Alzheimer’s disease (AD). Further studies to determine whether KYNA serves as a biomarker for cognitive decline and dementia progression are required. In this study, we measured CSF KYNA levels in AD patients (n = 19), patients with dementia with Lewy bodies (DLB) (n = 18), and healthy age-matched controls (Ctrls)) (n = 20) to further explore possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 54 publications
5
27
0
Order By: Relevance
“…Our analyses revealed a strong reduction in KA concentrations in CSF of PD and AD patients compared to agematched controls. This is in line with evidence of reduced post-mortem KA concentrations in a range of brain regions of PD patients (Ogawa et al 1992), reduced KA concentrations in CSF of PD and AD patients (Heyes et al 1992) and reduced cerebral KA levels in mouse models of AD (Zwilling et al 2011) although others showed no changes in KA concentrations in CSF in a small cohort of AD patients (Wennstrom et al 2014). In theory, reduced KA levels in the brain could result from reduced Kyn bioavailability or increased flux of Kyn through the 3-Hk/QA branch of the Kyn pathway.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our analyses revealed a strong reduction in KA concentrations in CSF of PD and AD patients compared to agematched controls. This is in line with evidence of reduced post-mortem KA concentrations in a range of brain regions of PD patients (Ogawa et al 1992), reduced KA concentrations in CSF of PD and AD patients (Heyes et al 1992) and reduced cerebral KA levels in mouse models of AD (Zwilling et al 2011) although others showed no changes in KA concentrations in CSF in a small cohort of AD patients (Wennstrom et al 2014). In theory, reduced KA levels in the brain could result from reduced Kyn bioavailability or increased flux of Kyn through the 3-Hk/QA branch of the Kyn pathway.…”
Section: Discussionsupporting
confidence: 86%
“…Disturbances of Kyn pathway metabolites in the blood of PD and AD patients are common (Widner et al 2000;Hartai et al 2007;Gulaj et al 2010;Schwarz et al 2013;Giil et al 2017;Havelund et al 2017;Chang et al 2018) but Kyn metabolites concentrations in cerebrospinal fluid (CSF), as a measure of their cerebral production, have been less well documented (Heyes et al 1992;Wennstrom et al 2014;Havelund et al 2017). In addition, with the exception of two (Giil et al 2017;Chang et al 2018), most of the abovementioned studies used a relatively small sample size and only one study analyzed Kyn metabolites in time-linked serum and CSF samples (Havelund et al 2017).…”
mentioning
confidence: 99%
“…The cellular distribution of the observed alterations in KAT activity and/or expression may have a special importance, because it was demonstrated that treatment of rats with sodium azide (an inhibitor of mitochondrial complex IV) altered the pattern of the expression of KAT-I in various relevant brain regions: the astroglial immunoreactivity was found to be decreased, whereas neurons started to express KAT-I [292]. With regard to the alterations of KYNA levels in human biological fluids with a possible biomarker value, decreased concentrations have been detected in the serum, plasma, and CSF of AD patients; however, recent studies have reported unaltered serum and CSF KYNA levels [232,234,257,293,294]. In one of these recent studies that did not find significant alteration in CSF KYNA level between AD patients and age-matched controls and revealed no associations between CSF KYNA level and cognitive dysfunctions in AD patients, CSF KYNA levels were, however, found to be significantly correlated with the AD-biomarker p-tau (hyperphosphorylated tau) and the inflammatory marker soluble intercellular adhesion molecule-1 [294].…”
Section: Kynurenic Acidmentioning
confidence: 99%
“…With regard to the alterations of KYNA levels in human biological fluids with a possible biomarker value, decreased concentrations have been detected in the serum, plasma, and CSF of AD patients; however, recent studies have reported unaltered serum and CSF KYNA levels [232,234,257,293,294]. In one of these recent studies that did not find significant alteration in CSF KYNA level between AD patients and age-matched controls and revealed no associations between CSF KYNA level and cognitive dysfunctions in AD patients, CSF KYNA levels were, however, found to be significantly correlated with the AD-biomarker p-tau (hyperphosphorylated tau) and the inflammatory marker soluble intercellular adhesion molecule-1 [294]. Furthermore, a gender difference was also demonstrated in this study, i.e., female AD patients had significantly higher CSF KYNA levels compared to the males, a difference not revealed in the control group.…”
Section: Kynurenic Acidmentioning
confidence: 99%
“…Additionally, increased levels of KYNA in the developing brain resulted in biochemical impairments and behavioral abnormalities [28]. However, several reports showing KYNA and other KP metabolite levels in CSF and blood from AD patients and healthy subjects reached inconclusive results [29][30][31][32][33][34][35]. Using high-performance liquid chromatography (HPLC), recent studies found increased KYNA concentration in CSF in different cohorts of AD patients [36,37].…”
Section: Introductionmentioning
confidence: 99%